Electrostatic self-assembled carbon nanotube/nano carbon black composite fillers reinforced cement-based materials with multifunctionality. (December 2015) - Han, Baoguo; Zhang, Liqing; Sun, Shengwei; Yu, Xun; Dong, Xufeng; Wu, Tianjiao; Ou, Jinping
Abstract: Electrostatic self-assembled carbon nanotube (CNT)/nano carbon black (NCB) composite fillers are added into cement mortar to fabricate smart cement-based materials. The grape bunch structure of CNT/NCB composite fillers is beneficial for dispersing CNT/NCB in cement mortar matrix and achieving cooperative improvement effect. The mechanical, electrically conductive, and piezoresistive behaviors of the cement mortar are investigated. The CNT/NCB composite fillers can effectively enhance the flexural strength and electrical conductivity of cement mortars, and endow stable and sensitive piezoresistivity to cement mortar at a low filler content. However, they weaken the compressive strength of cement mortar to some extent. The percolation threshold zone of cement mortar with CNT/NCB composite fillers ranges in the amount of 0.39–1.52 vol.%. The optimal content of CNT/NCB composite fillers is 2.40 vol.% for piezoresistivity and the stress and strain sensitivities can reach 2.69% MPa −1 and 704, respectively.